3D periodic multiscale TiO2 architecture: a platform decorated with graphene quantum dots for enhanced photoelectrochemical water splitting. (15th February 2016) - Xu, Zhen; Yin, Min; Sun, Jing; Ding, Guqiao; Lu, Linfeng; Chang, Paichun; Chen, Xiaoyuan; Li, Dongdong
Abstract: Micropatterned TiO2 nanorods (TiO2 NRs) via three-dimensional (3D) geometry engineering in both microscale and nanoscale decorated with graphene quantum dots (GQDs) have been demonstrated successfully. First, micropillar (MP) and microcave (MC) arrays of anatase TiO2 films are obtained through the sol–gel based thermal nanoimprinting method. Then they are employed as seed layers in hydrothermal growth to fabricate the 3D micropillar/microcave arrays of rutile TiO2 NRs (NR), which show much-improved photoelectrochemical water-splitting performance than the TiO2 NRs grown on flat seed layer. The zero-dimensional GQDs are sequentially deposited onto the surfaces of the microscale patterned nanorods. Owing to the fast charge separation that resulted from the favorable band alignment of the GQDs and rutile TiO2, the MP-NR-GQDs electrode achieves a photocurrent density up to 2.92 mA cm −2 under simulated one-sun illumination. The incident-photon-to-current-conversion efficiency (IPCE) value up to 72% at 370 nm was achieved on the MP-NR-GQDs electrode, which outperforms the flat-NR counterpart by 69%. The IPCE results also imply that the improved photocurrent mainly benefits from the distinctly enhanced ultraviolet response. The work provides a cost-effective and flexible pathway to develop periodic 3D micropatterned photoelectrodes and is promising for the future deployment of high performance optoelectronic devices.